The Exploration Local of Control in Physics Learning: Conductiong Survey Research - Al Wachidy, Muchammad Chabibur Rochman; Handayanto, Supriyono Koes (Graduate School of Universitas Negeri Malang, 2023)
The aim of this research to explore the level of Locus of Control students towards learning physics and to examine the interrelationship between the dimensions of Locus of Control in Physics Learning. A total of 215 students majored in Natural Sciences Senior High School who as the participants of this study and were invited to complete the instrument: Locus of Control in Physics Learning (LOCPL). The Locus of Control questionnaire was developed from Rotter (1966) and validated through an Exploratory Factor Analysis of participants' responses and Pearson Correlation Product Moment is used to measure the level of interrelation between dimensions. The results show that first, the validity and reliability instruments used in the study have a satisfactory level. Second, the value of the construct validity of the LOC instrument that varies from the numbers 0.415-0.782 with a total variance explained = 60.674%. Overall the value of the Cronbach's alpha coefficient instrument gets 0.607 results. The LOCI dimension occupies the first position in the LOC factor level, followed by LOCII and LOCIII. Then the results show that the interrelationship between each of the dimensions Locus of Control are significant.